2015
DOI: 10.1038/srep15179
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor-infiltrating FoxP3+ regulatory T cells in cancers: a systematic review and meta-analysis

Abstract: The prognostic value of FoxP3+ regulatory T cells (Tregs) in cancer remains controversial. We did a meta-analysis to assess the prognostic effect of FoxP3+ Treg across different types of cancer and to investigate factors associated with variations in this effect. PubMed, Embase, Cochrane CENTRAL, and Scopus were searched to identify eligible studies. In total, we analyzed 76 articles encompassing 17 types of cancer, and including 15,512 cancer cases. The overall pooled analysis including all types of cancer su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
638
8
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(694 citation statements)
references
References 50 publications
40
638
8
8
Order By: Relevance
“…In the majority of cancers, Treg cells demonstrate a marked negative effect on patient prognosis. High FoxP3 + Treg infiltration is strongly associated with a shorter overall survival in patients with melanoma whereas in other indications the impact of Treg cells is less clear 46. In this study, we demonstrate in an in vitro killing assay, that Treg cells used at an equal proportion with cytotoxic T cells fail to affect IMCgp100‐mediated target cell apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…In the majority of cancers, Treg cells demonstrate a marked negative effect on patient prognosis. High FoxP3 + Treg infiltration is strongly associated with a shorter overall survival in patients with melanoma whereas in other indications the impact of Treg cells is less clear 46. In this study, we demonstrate in an in vitro killing assay, that Treg cells used at an equal proportion with cytotoxic T cells fail to affect IMCgp100‐mediated target cell apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…CD4 1 CD25 1 CD127 -/low T regs , a subpopulation of CD4 1 T cells, help to maintain immune homeostasis by inhibiting immune responses under physiological conditions [19]. Recently, emerging evidence indicated that the proportion of T regs is increased in various types of solid tumour, which is associated with poor prognosis [31]. However, the effect of CSCs on the recruitment of T regs remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that tumour cells develop potent, overlapping mechanisms to foster immune privilege by including the infiltration of T regs into the tumour microenvironment [27][28][29][30]. T regs enriched in ovarian carcinoma lead to reduced survival [27] and this has also been observed in many other solid tumours, including melanomas, renal cancer, breast cancer, cervical cancer [31] and colorectal cancer [32]. T regs infiltrate into tumour sites via various mechanisms, such as trafficking, differentiation, expansion and conversion [33].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, decreased ratios of tumor-infiltrating CD8 + T cells to FOXP3 + Treg cells were shown to correlate with poor prognosis, especially in patients with breast [51], gastric [46], and ovarian cancer [48,49]. Furthermore, a recent meta-analysis of previously published data indicated that in majority of solid tumors in the cervix, kidney, breast, and melanomas, high frequency of tumor-infiltrating FOXP3 + cells was significantly negatively correlated with patients' survival [52].…”
Section: Tumor-infiltrating Treg Cellsmentioning
confidence: 99%